Dispersion modeling of NOx from stacks of cracking furnaces of OLEFIN unit using AERMOD - Iman Jalali; Somayeh Tourani (Results in Chemistry)
The essential constant sources of air pollution can be vehicles, chemical units, power plants, crude oil refineries, petrochemical units, and other large industries. Nitrogen oxides (NOx) are global byproducts of high-temperature combustion processes and are considered harmful to the atmosphere. The abatement of NOx emissions is crucial in both stationary and mobile applications.The main goal of this study was to model the emission of NOx from the stacks of cracking furnaces at the Amirkabir petrochemical company. AERMOD was used to model the dispersion and concentration of nitrogen oxides (NOx) emitted from the stacks of the olefin cracking furnaces at the Amirkabir petrochemical facility using the AERMOD dispersion model. The researchers then compared the estimated NOx pollutant levels from the model with the actual field measurements. The study was conducted in the Petrochemical Special Economic Zone (PSEZ) located near Bandar Imam, Iran, which houses the Amirkabir petrochemical plant.The air modeling demonstrated that the maximum output concentrations of NOX were 1221 μg/m3 in the spring, 2039 μg/m3 in the summer, 1078 μg/m3 in the autumn, 1164 μg/m3 in the winter, and 1716.527 μg/m3 for the whole year. Since the prevailing wind is from the northwest, NOX does not significantly affect populated centers. Additionally, the output concentrations did not exceed the standard limits in all urban and residential areas. Finally, the study results indicate that the pollutant concentrations obtained from the model are lower than the measured values. This may be due to incomplete pollutant sources, not considering other company buildings around the desired location, inaccurate upper air measurement data estimated by AERMOD, and insufficient field test data included in the analysis.